The EFFECT OF BEVACIZUMAB ON ANGIOGENESIS INTRABECULECTOMY AREA - Diana Yuliawati (Journal of Stem Cell Research and Tissue Engineering, 2022)
Objective to examine the effect of Bevacizumab injection to the angiogenesis which the amount and density of blood vessel as the indicators after trabeculectomy procedure. Method This was a true experimental study using 16 eyes of 16 New Zealand White Rabbit eye treated by trabeculectomy procedure with eight eyes as the control group using Balanced Saline Solution (BSS) and eight eyes as the treatment group using Bevacizumab. It was injected subconjuctiva after the trabeculectomy. At the end of the study all rabbits in each group was sacrified, the eye was enucleated and the bleb area was dissected, and then processed for histological studies. The amount and density of blood vessel were evaluated using haematoxyllin eosin methode at day 14 after the eyes was done for trabeculectomy procedure. Result The mean of amount of blood vessel in control group was 22,63 ± 11,02 and treatment group was 14,75 ± 4,92 (p=0.043). The mean of density of blood vessel in control group was 19,10 ± 1,69 % and treatment group was 16,53 ± 2,90 % (p=0.029)%. The result shows there were statistically significant difference between the two groups (p<0.05). Conclusion In this study the subconjunctival Bevacizumab injection after trabeculectomy reduce the amount and density of blood vessel compared with subconjunctival BSS injection only, thus it is potential in preventing subconjunctival fibrosis after trabeculectomy